The forbidden fruit: using the mother tongue in a Bogota university EFL programme - Fortune, Jill (Colombian Applied Linguistics Journal, 2012)
The current debate on the use of the mother tongue in the foreign language classroom has led to a wide array of literature being written on the subject. While this can be enlightening, it can also cause confusion and anxiety among teachers when faced with the question of whether or not it is acceptable to use the L1 in class. This paper analyses current perceptions and practices in terms of L1 use among teachers and students in the EFL and ESL settings, based on the hypothesis that the use of the L1 to some degree could be beneficial to EFL learners. Teacher and student activity and opinions are analysed through surveys and interviews before being compared and contrasted with classroom reality through live observation. The findings confirm that L1 use could indeed be beneficial to EFL learners, particularly at the lower levels of language proficiency, but that teachers may need to revisit their reasons for using the L1, as well as their repertoire of pro-L2-use strategies.